(untitled) (Biological Sciences - PJSIR, 1999)
Synthesis of5-(substituted phenylazo) uracil compounds (I) have been reported. The analytical data and ’H-NMR are used to elucidate the structures. The electronic spectral properties of the organic compounds were investigated in presence of different solvents and at different pH’s. The pK’s values were determined and related with the molecular structure of the compounds. The electronic transitions were assigned. The phenomenon of tautomerism was explained. The shifts in peak locations in the electronic spectra of the organic compounds have been correlated with different solvent polarity parameters.